Valproic Acid Induces Cutaneous Wound Healing In Vivo and Enhances Keratinocyte Motility - Lee, Soung-Hoon; Zahoor, Muhammad; Hwang, Jae-Kwan; Min, Do Sik; Choi, Kang-Yell (PLOS ONE, 2012)
Background Cutaneous wound healing is a complex process involving several signaling pathways such as the Wnt and extracellular signal-regulated kinase (ERK) signaling pathways. Valproic acid (VPA) is a commonly used antiepileptic drug that acts on these signaling pathways; however, the effect of VPA on cutaneous wound healing is unknown. Methods and Findings We created full-thickness wounds on the backs of C3H mice and then applied VPA. After 7 d, we observed marked healing and reduced wound size in VPA-treated mice. In the neo-epidermis of the wounds, β-catenin and markers for keratinocyte terminal differentiation were increased after VPA treatment. In addition, α-smooth muscle actin (α-SMA), collagen I and collagen III in the wounds were significantly increased. VPA induced proliferation and suppressed apoptosis of cells in the wounds, as determined by Ki67 and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining analyses, respectively. In vitro, VPA enhanced the motility of HaCaT keratinocytes by activating Wnt/β-catenin, ERK and phosphatidylinositol 3-kinase (PI3-kinase)/Akt signaling pathways. Conclusions VPA enhances cutaneous wound healing in a murine model and induces migration of HaCaT keratinocytes.